Potentially modifiable predictors of mortality in patients treated with long-term oxygen therapy - Lima, Daniela F. [UNESP]; Dela Coleta, Karina [UNESP]; Tanni, Suzana E. [UNESP]; Silveira, Liciana Vaz de Arruda [UNESP]; Godoy, Ilda de [UNESP]; Godoy, Irma de [UNESP] (W B Saunders Co Ltd, 2011)
Introduction: Anemia is considered a systemic manifestation of Chronic Obstructive Pulmonary Disease (COPD); however, few studies have described its influence on chronic respiratory failure (CRF) prognosis. We aimed to test the hypotheses that anemia negatively influences survival and also to identify the cut-off points of hematocrit (Htc) and hemoglobin (Hb) associated with higher mortality in CRF patients using long-term oxygen therapy (LTOT). Methods: One-hundred forty two patients with CRF in use of LTOT were evaluated at baseline and followed for three years or until death. Baseline assessment included identification, diagnosis, body composition, dyspnea, health status (HS), spirometry, arterial blood gases, Hb and Htc. Univariate and Cox proportional hazard models were used to evaluate predictors of mortality. We performed ROC curve to identify the best cut-off point of the variables related to survival to construct the Kaplan-Meier curves.Results: Eight-three patients (58%) died after three years. Baseline values of Hb and Htc were significantly lower in the non-survivors group and both, Htc (HR, 0.96; 95%Cl 0.91-0.99; p = 0.04), Hb (HR, 0.86; 95%Cl 0.76-0.98; p = 0.02) were selected as predictors of mortality after three years. The cut-off points determined were: the value of HB is < 11g/dl (sensitivity 95% specificity 85%), Htc <= 33% (sensitivity 97% specificity 89%). Other prognostic factors were: male gender, low PaCO2 and SpO(2), higher dyspnea perception and impairment of HS.Conclusions: Our study shows that anemia is a predictor of mortality in patients with CRF under LTOT treatment. Although anemia is potentially modifiable, the effects of raising hemoglobin on mortality remain undetermined. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Chronic respiratory failure; Long-term oxygen therapy; Predictors of mortality; COPD; Hemoglobin; Hematocrit